Is hyaluronan deposition in the stroma of pancreatic ductal adenocarcinoma of prognostic significance? - Florian Gebauer; Marius Kemper; Guido Sauter; Peter Prehm; Udo Schumacher (PLoS ONE)
Background Pancreatic ductal adenocarcinoma (PDAC) has a dismal prognosis and the number of PDAC-related deaths is rising. Recently the tumour stroma and in particular one of its main components, hyaluronan (HA), have attracted considerable attention as intravenous hyaluronidase treatment together with conventional chemotherapy considerably prolonged survival in HA-rich PDA patients. We therefore wanted to investigate the prognostic significance of HA deposition in PDA using both antibodies to HA and hyaluronan binding protein (HABP). Material and methods Tissue microarrays of PDAs of 184 patients and pancreatic xenografts tumours were immunohistochemically (IHC) stained for HA using either biotinylated hyaluronic acid binding protein (HABP) or anti-HA antibody. Results The pattern of staining with HABP differed significantly from that with antibody IHC. Antibody staining was found both within cancer cells and in the extracellular matrix and staining could not be eliminated by hyaluronidase predigestion of the tissue sections. In contrast, HABP staining was generally confined to the extracellular matrix and was completely abolished by hyaluronidase pretreatment. HA positivity as determined by HABP was associated with larger primary tumours (p = 0.046). There were no correlations between overall survival, disease-free survival and HA expression. Conclusion Presence of HA alone is not of prognostic importance in PDAC, and IHC with utilization of antibody detection shows no reliable staining pattern and should not be applied for HA IHC.